Efficacy evaluation of a commercial neem cake for control of Haematobia irritans on nelore cattle - de Souza Chagas, Ana Carolina; de Sena Oliveira, Márcia Cristina; Giglioti, Rodrigo [UNESP]; Calura, Fernando Henrique; Ferrenzini, Jenifer; Forim, Moacir Rossi; de Barros, Antonio Thadeu Medeiros (My University, 2010)
Much attention has been given to the development of botanical insecticides to provide effective natural control of cattle ectoparasites without harming animals, consumers, and environment. This study evaluated the efficacy of a commercial neem cake in controlling Haematobia irritans infestation on cattle. The study was conducted at the Embrapa Southeast Cattle Research Center (CPPSE), in São Carlos, SP, Brazil, from April to July 2008. The neem cake mixed in mineral salt in a 2% concentration was provided to 20 Nelore cows during nine weeks and had its efficacy evaluated by comparison of the infestation level against a control group. Fly infestations were recorded weekly by digital photographs of each animal from both groups and the number of flies was later counted in a computer-assisted image analyzer. Quantification of neem cake components by high-performance liquid chromatography revealed the presence of azadirachtin (421 mg.kg-1) and 3-tigloyl-azadirachtol (151 mg.kg-1) in the tested neem cake. Addition of the 2% neem cake reduced mineral salt intake in about 22%. The 2% neem cake treatment failed to reduce horn fly infestations on cattle during the 9-week study period.
avaliação da eficácia de uma torta comercial de nim para o controle de haematobia irritans em bovinos nelore
Keywords: 3-tigloyl-azadirachtol; Azadirachtin; Horn fly; Phytotherapy; Plant extract